Early cellular and synaptic changes in dopaminoceptive forebrain regions of juvenile mice following gestational exposure to valproate - Finszter, Cintia Klaudia; Kemecsei, Róbert; Zachar, Gergely; Holtkamp, Sophie; Echevarría, Diego; Adorján, István; Ádám, Ágota; Csillag, András (Frontiers in Neuroanatomy, 2023)
Gestational exposure of mice to valproic acid (VPA) is one currently used experimental model for the investigation of typical failure symptoms associated with autism spectrum disorder (ASD). In the present study we hypothesized that the reduction of dopaminergic source neurons of the VTA, followed by perturbed growth of the mesotelencephalic dopamine pathway (MT), should also modify pattern formation in the dopaminoceptive target regions (particularly its mesoaccumbens/mesolimbic portion). Here, we investigated VPA-evoked cellular morphological (apoptosis-frequency detected by Caspase-3, abundance of Ca-binding proteins, CaBP), as well as synaptic proteomic (western blotting) changes, in selected dopaminoceptive subpallial, as compared to pallial, regions of mice, born to mothers treated with 500 mg/kg VPA on day 13.5 of pregnancy. We observed a surge of apoptosis on VPA treatment in nearly all investigated subpallial and pallial regions; with a non-significant trend of similar increase the nucleus accumbens (NAc) at P7, the age at which the MT pathway reduction has been reported (Ádám et al. 2020, supplemented by current findings). Of the CaBPs , calretinin (CR) expression was decreased in pallial regions, most prominently in retrosplenial cortex, but not in the subpallium of P7 mice. Calbindin-D 28K (CB) was selectively reduced in the caudate-putamen (CPu) of VPA exposed animals at P7 but no longer at P60, pointing to a potency of repairment. The VPA-associated overall increase in apoptosis at P7 did not correlate with the abundance and distribution of CaBPs, except in CPu, in which the marked drop of CB was negatively correlated with increased apoptosis. Abundance of parvalbumin (PV) at P60 showed no significant response to VPA treatment in any of the observed regions We did not find colocalization of apoptotic (Casp3+) cells with CaBP-immunoreactive neurons. The proteomic findings suggest reduction of tyrosine hydroxylase in the crude synaptosome fraction of NAc, but not in the CPu, without simultaneous decrease of the synaptic protein, synaptophysin, indicating selective impairment of dopaminergic synapses. The morpho-functional changes found in forebrain regions of VPA-exposed mice may signify dendritic and synaptic reorganization in dopaminergic target regions, with potential translational value to similar impairments in the pathogenesis of human ASD.